Blastomycosis in Africa and the Middle East: A Comprehensive Review of Reported Cases and Reanalysis of Historical Isolates Based on Molecular Data. (7th August 2020) - Schwartz, Ilan S; Muñoz, Jose F; Kenyon, Chris R; Govender, Nelesh P; McTaggart, Lisa; Maphanga, Tsidiso G; Richardson, Susan; Becker, Pierre; Cuomo, Christina A; McEwen, Juan G; Sigler, Lynne
Abstract: Background: Blastomycosis has been reported from countries in Africa and the Middle East, but a decades-long debate has persisted regarding whether this is the same disease known in North America and caused by Blastomyces dermatitidis and Blastomyces gilchristii . Methods: We reviewed published cases of human and veterinary blastomycosis from Africa and the Middle East. We abstracted epidemiological and clinical features of cases, including sites of disease, diagnosis, management, outcomes, and, where available, genetic and antigenic typing of case isolates. In addition, we sequenced nucleic acids from 9 clinical isolates from Africa deposited in global collections as B. dermatitidis ; for 5, we sequenced the internal transcribed spacer regions, and for the other 4 we sequenced the whole genomes. Results: We identified 172 unique human patients with blastomycosis, including 159 patients from 25 African countries and 12 patients from 5 Middle Eastern countries, and also identified 7 reports of veterinary blastomycosis. In humans, cutaneous disease predominated (n = 100/137, 73%), followed by pulmonary (n = 73/129, 57%) and osteoarticular involvement (n = 61/128, 48%). Unusual direct microscopy/histopathological presentations included short hyphal fragments in tissues (n = 23/129, 18%). There were 34 genotyped case isolates that comprised 4 species: Blastomyces percursus (n = 22, 65%), from 8 countries throughout all regions; Blastomyces emzantsi (n = 9, 26%), from South Africa; B. dermatitidis (n = 1, 3%), from the Democratic Republic of Congo; and B. gilchristii (n = 2, 6%), from South Africa and Zimbabwe. Conclusions: Blastomycosis occurs throughout Africa and the Middle East and is caused predominantly by B. percursus and, at least in South Africa, B. emzantsi, resulting in distinct clinical and pathological patterns of disease. Abstract : Blastomycosis occurs throughout Africa and Middle East and is clinically and microbiologically distinct from the disease in North America. Cutaneous and osteoarticular involvement are common, and causative pathogens are Blastomyces percursus, Blastomyces emzantsi, and, rarely, Blastomyces dermatitidis and Blastomyces gilchristii .